Keanekaragaman Vegetasi Pada Hutan Penyangga di Kabupaten Manokwari - Mahmud (Program Pascasarjana Universitas Papua, 2024)
ABSTRACT: Currently, limited production forest (LPF) or the buffer zone are targeted in relation to the need for food and the development of new autonomous regions. This study aims to determine the diversity of species and structure in the buffer zone from seedlings to trees in the Arui Watershed, Manokwari Regency. Samples were taken using systematic sampling, vegetation structure was determined based on the importance value index while species diversity analysis was determined based on the Shannon-Wiener index. The results showed that there were 92 plots with 84 species of 43 families with a species diversity of 1,6-1,9 which was classified as moderate. The four dominant species that are often found at the seedling, sampling, pole and tree levels are: Horsfieldia irya, Pometia pinnata, Chisocheton ceramicus and Teijsmanniodendron bogoriense. Hydrology, land, biodiversity and social diversity need to be reconsidered in non-forest sector development so that the threat of flooding does not recur.